Pengembangan Kurikulum Pendidikan Bahasa Arab bagi Penutur Bahasa Indonesia (Orang yang Berbahasa Indonesia) - Rahmatullah, Syarifatur (SYAMIL: Journal of Islamic Education, 2014)
Curriculum development is a necessity for a teacher or an institutionwhere they work. Curriculum development is done in order to answerthe needs of learners that will be taught with materials they need. Thesame thing was also applied to the Arabic learning curriculum. Arabicthat used to be assumed as the language of religion, has turned into aninternational language that is not only synonymous with a religiontoday. Then, learning Arabic curriculum development should besuitable to answer the development of assumptions about the Arabiclanguage. This paper tries to provide a reference and guide for teachersor institutions in developing Arabic curriculum for Indonesian studentswho are not the native speakers of Arabic.